TIGA RATUS TAHUN LINNEAUS - SUATU PENGANTAR - Sukara, Endang (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Three hundred years ago, a Sweden expert, Carl von Linne had laid down a very basic and strong foundation in naming all the living organisms on earth.Supposedly, without the brilliant effort of Carl von Linn6, nowadays, there may have any chaos among people around the world in naming all the living creatures, because everyone would have given the name to those organisms, due to their own sense; thus a kind species may have thousands of name. If this is happen, then all the information regarding the species (including its benefit to mankind) may have no meaning at all. All people would have spoken about a species differently, without realize that they actually regarding about the same species.The center of references such as Herbarium Bogoriense and Museum Zoologicum Bogoriense may be not existed without the work and service of Carolus Linnaeus. No one nowadays arguing the great service of Carolus Linnaeus in naming of each living organisms based on binomial nomenclature.